You are on page 1of 3

# A simple proof of the Initial and Final Value Theorems

## Torbjörn Nordling October 15, 2007

E-mail: tn@kth.se

## Theorems and definitions

Initial value theorem
If and only if the linear time invariant system producing x(t) is stable then

t→0 s→∞

## Final value theorem

If and only if the linear time invariant system producing x(t) is stable then

## lim x(t) = lim sX(s)

t→∞ s→0

Stable
Consider a system ẋ(t) = f (x, t) as t ≥ 0 and suppose that x0 is an equilibrium and that the system
has a unique solution for each initial condition in the domain of interest. The equilibrium x0 is stable
if and only if

## ∃δ(, t0 ) such that ∀ > 0, t ≥ t0 ≥ 0 kx0 − x0 k < δ(, t0 ) ⇒ kx(x0 , t, t0 ) − x0 k < .

Proof
Consider a system ẋ(t) = f (x) as t ≥ 0. Assume that x(t) is piece-wise continuous and that all left and
right side limits are well defined. Let limγ→0 denote the limit along the positive real axis from above
and limγ→∞ along the positive real axis from below. (The proof is valid for generalized functions too,
even though I am avoiding the 0+ , 0− issue of  by indicating the direction of the limit with signs in
front of the variables). The Laplace transform of the time derivative of x(t) is
  Z υ  Z b Z b 
d d −st 0 b 0
L− x(t) ≡ lim lim x(t)e dt = partial integration: f g = [f g]a − fg
dt υ→∞ →0 − dt a a
Z υ
−st υ
x(t)(−s)e−st dt
 
= lim lim x(t)e −
− lim lim
υ→∞ →0 υ→∞ →0 −
Z υ
= 0 − lim x(−) + s lim lim x(t)e−st dt = − lim x(−) + sX(s).
→0 υ→∞ →0 − →0
| {z }
L− (x(t))

Here lim→0 x(−) denotes the pre-initial value (see ). If we now take the limit when s → ∞ of the
two underlined terms then we get
Z υ "Z #
 Z υ
d −st d 0 d −st
lim lim lim x(t)e dt = lim lim lim x(t) |{z}
e dt + x(t)e dt
s→∞ υ→∞ →0 − dt υ→∞ →0 s→∞ − dt  dt
=1
= lim [x(t)]− + 0 = lim x() − lim x(−)
→0 →0 →0

1
and
h i
lim − lim x(−) + sX(s) = − lim x(−) + lim sX(s)
s→∞ →0 →0 s→∞

hence

## − lim x(−) + lim sX(s) = lim x() − lim x(−)

→0 s→∞ →0 →0

lim x(t) = lim sX(s)
t→0 s→∞

## gives the initial value theorem.

If we instead take the limit when s → 0 of the two underlined terms then we get
Z υ Z υ
d
lim lim lim −st
x(t)e dt = lim lim dx(t) = lim lim [x(t)]υ−
s→0 υ→∞ →0 − dt υ→∞ →0 − υ→∞ →0

## = lim x(υ) − lim x(−)

υ→∞ →0

and
h i
lim − lim x(−) + sX(s) = − lim x(−) + lim sX(s)
s→0 →0 →0 s→0

hence

## − lim x(−) + lim sX(s) = lim x(υ) − lim x(−)

→0 s→0 υ→∞ →0

lim x(t) = lim sX(s)
t→∞ s→0

## gives the final value theorem.

In order for the relationships to hold the Laplace transform L− (x(t)) must exist, i.e. the integral
must converge or similarly both the upper and lower limits of
Z υ
L− (x(t)) = lim lim x(t)e−st dt
υ→∞ →0 −

must be finite. That is x(t) must be of exponential type, i.e. |x(t)| < eM t for all large t. Then the
integral converges for all <(s) > M . Let us take two examples where we get convergence problems
and thus derive the demand that the system must be stable.
If we assume x(t) = Aeαt , where A and α are real-valued constants, i.e. a single real pole, and
insert it then
1 (α−s)t υ
Z υ Z υ  
αt αt −st (α−s)t

L− Ae = lim lim Ae e dt = A lim lim e dt = A lim lim e
υ→∞ →0 − υ→∞ →0 − υ→∞ →0 α − s
−
 
A   lim e(α−s)υ − lim e−(α−s)  = A .

=
α − s  |υ→∞ {z } →0
| {z }
 s−α
=0 iff <(s)≥α =1

In the final value theorem we take the limit when s → 0, and the Laplace transform above must exist
even in that case, so a necessary condition is α ≤ 0, i.e. that the poles of the system is in the left
hand halfplane and it is stable.
If we instead assume x(t) = eαt (A cos βt + B sin βt), where A,B, α and β are real-valued constants,

2
i.e. a pair of complex conjugated poles p = α ± iβ, then we get
Z υ
L− eαt (A cos βt + B sin βt) = lim lim (A cos βt + B sin βt)eαt e−st dt

υ→∞ →0 −
 Z υ Z υ 
(α−s)t (α−s)t
= lim lim A e cos βt dt + B e sin βt dt
υ→∞ →0 − −

1
= {Beta p.175} = lim lim e(α−s)t
υ→∞ →0 (α − s)2 + β 2
 υ

## A(α − s) cos βt + Aβ sin βt + B(α − s) sin βt − Bβ cos βt

 
| {z }
(Bα+Aβ−Bs) sin βt+(Aα−Bβ−As) cos βt
 −
(Bα + Aβ − Bs)  lim e(α−s)υ sin βυ − lim e−(α−s) sin(−β)

=
(α − s)2 + β 2  υ→∞
| {z } →0
| {z }

=0 iff <(s)>α =0
 
(Aα − Bβ − As) 
 lim e(α−s)υ cos βυ − lim e−(α−s) cos(−β)

+ 2 2
(α − s) + β υ→∞
| {z } →0
| {z }

=0 iff <(s)>α =1
A(α − s) − Bβ A(s − α) + Bβ
= − = .
(α − s)2 + β 2 (s − α)2 + β 2

In the final value theorem we take the limit when s → 0, and the Laplace transform above must exist
even in that case, so a necessary condition is α < 0, i.e. that the poles of the system is strictly in the
left hand halfplane and it is asymptotically stable. In general the solution to a linear time invariant
homogeneous ODE can be expressed as

## where Pn (t) are polynomials of t and λn ∈ C. Since

Z Z
λt 1 λt 1 dP (t) λt
P (t)e dt = P (t)e − e dt (2)
λ λ dt

the critical condition will also in the general case be <(λ) ≤ 0 or <(λ) < 0, i.e. all poles except one,
which may be in the origin, should be in the open left halfplane. We have thus shown that a sufficient
and necessary condition for the final value theorem is that the system is stable.

References
 Kent H. Lundberg, Haynes R. Miller, and David L. Trumper. Initial conditions, generalized
functions, and the laplace transform troubles at the origin. Control Systems Magazine, IEEE,
27:22–35, 2007.